An Integrated Resilient Sediment Transport RIsk Management (IRSTRIM) Approach for Estuaries - Mina Zakipour; Farhad Yazdandoost; Karim Alizad; Ardalan Izadi; Aref Farhangmehr (Journal of Marine Science and Engineering, 2023)
Estuaries around the world are facing numerous threats, including urbanization, industrialization, resource scarcity, and the impacts of climate change. To increase estuarine resilience, it is crucial to manage these ecosystems to maintain their functionality. Sediment transport resilience is a critical factor that affects the performance objectives of navigation, storm damage reduction, and ecosystem restoration. This paper focuses on an integrated resilient sediment transport risk management (IRSTRIM) approach for estuaries. The framework quantifies resilience indexes such as reaction amplitude, graduality, and recovery rates of “sediment transport” to “river and sea interaction” in the Arvand Estuary, the Persian Gulf. Additionally, three indexes, the tidal asymmetry index (TAI), saltwater intrusion vulnerability index, and infill rate, are developed to aid in resilient sediment management. The quantified indexes successfully incorporated tidal asymmetry, sediment characteristics, bed properties, and flow hydrodynamics. Different resilience and resistance management scenarios are evaluated using a decision support system. Based on the results, tidal barrier application, as a resilience scenario, is the best scenario, and the dredging scenario, as a resistance one, is the worst scenario. The reaction amplitude with a weight of 0.39, and the TAI with a weight of 0.27 are determined as the most effective indexes.